Cross Talk Between Cyclic Nucleotides and Calcium Signaling Pathways in Plants–Achievements and Prospects - Świeżawska-Boniecka, Brygida; Duszyn, Maria; Kwiatkowski, Mateusz; Szmidt-Jaworska, Adriana; Jaworski, Krzysztof (Frontiers in Plant Science, 2021)
A variety of plant cellular activities are regulated through mechanisms controlling the level of signal molecules, such as cyclic nucleotides (cNMPs, e.g., cyclic adenosine 3':5'-monophosphate, cAMP, and cyclic guanosine 3':5'- monophosphate, cGMP) and calcium ions (Ca2+). The mechanism regulating cNMP levels affects their synthesis, degradation, efflux and cellular distribution. Many transporters and the spatiotemporal pattern of calcium signals, which are transduced by multiple, tunable and often strategically positioned Ca2+-sensing elements, play roles in calcium homeostasis. Earlier studies have demonstrated that while cNMPs and Ca2+ can act separately in independent transduction pathways, they can interact and function together. Regardless of the context, the balance between Ca2+ and cNMP is the most important consideration. This balance seems to be crucial for effectors, such as phosphodiesterases, cyclic nucleotide gated channels and cyclase activity. Currently, a wide range of molecular biology techniques enable thorough analyses of cellular cross talk. In recent years, data have indicated relationships between calcium ions and cyclic nucleotides in mechanisms regulating specific signaling pathways. The purpose of this study is to summarize the current knowledge on nucleotide-calcium cross talk in plants.